Diagnosis, treatment, and effects of the crisis in Greece: A 'special case' or a 'test case'? - Maria Markantonatou (Max Planck Institute for the Study of Societies, 2013)
This paper discusses the management of the crisis in Greece, arguing that it was based on a series of diagnoses that justified fiscal discipline by stigmatizing the Greek economy and society, and that it had a narrow understanding of the reasons for Greece's deteriorating competitiveness. I begin by critically examining a series of diagnoses that take a 'rent-seeking' approach as a common starting point. I then argue that the chosen treatment of 'internal devaluation' was based on questionable perceptions of labor costs and public expenditure during the pre-crisis period in Greece, a treatment which then aggravated recession. I follow up with an overview of the socio-political consequences of the crisis (unemployment, poverty, social deregulation, rise of neofascism). In conclusion, I point to the premises of methodological nationalism, both in neoliberal and neo-Keynesian understandings of the crisis. Such views disregard the fact that states have prioritized the strengthening of the global financial system and its rescue in times of crisis, as well as the process of a deepening neoliberalism within the EU - even at a constitutional level through the Fiscal Compact - in which management of the Greek crisis has been inscribed. – – Der Beitrag analysiert das Management der Krise in Griechenland. Grundlage des Krisenmanagements, so die Argumentation, waren Diagnosen, die über eine Stigmatisierung der griechischen Wirtschaft und Gesellschaft eine strengere Haushaltsdisziplin rechtfertigten, sowie ein allzu eng gefasstes Verständnis der schwindenden Wettbewerbsfähigkeit des Landes. Ausgehend von einer kritischen Bestandsaufnahme des 'Rent-Seeking'-Ansatzes wird dargelegt, dass die gewählte Strategie der 'internen Abwertung' nicht nur auf einer fragwürdigen Beurteilung der Entwicklung von Lohnkosten und öffentlichen Ausgaben während der Vorkrisenperiode in Griechenland beruht, sondern auch die wirtschaftliche Rezession verschärft hat. Schließlich bietet der Beitrag einen Überblick über die soziopolitischen Konsequenzen der Krise (Unterbeschäftigung, Armut, soziale Deregulierung, Neofaschismus). Sowohl das neoliberale wie auch das neo-keynesianische Krisenverständnis beruhen auf den Prämissen des methodologischen Nationalismus. Diese Betrachtungsweise lässt jedoch außer Acht, dass Staaten der Rettung und Stärkung des globalen Finanzsystems in Krisenzeiten höchste Priorität einräumen und dass das Management der Krise in Griechenland durch den Europäischen Fiskalpakt auch auf konstitutioneller Ebene mit dem Vertiefungsprozess des Neoliberalismus in der Europäischen Union verwoben ist.
Keywords: 300